2013
DOI: 10.1051/0004-6361/201321391
|View full text |Cite
|
Sign up to set email alerts
|

Structure of sunspot penumbral filaments: a remarkable uniformity of properties

Abstract: Context. The sunspot penumbra comprises numerous thin, radially elongated filaments that are central for heat transport within the penumbra, but whose structure is still not clear. Aims. We aim to investigate the fine-scale structure of these penumbral filaments. Methods. We perform a depth-dependent inversion of spectropolarimetric data of a sunspot very close to solar disk center obtained by Solar Optical Telescope/Spectropolarimeter onboard the Hinode spacecraft. We have used a recently developed, spatially… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
205
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(241 citation statements)
references
References 104 publications
(188 reference statements)
36
205
0
Order By: Relevance
“…1, is the granular flow pattern that is clearly visible around both the sunspots. This contrasts with the penumbra, that shows many compact regions containing predominantly upflows in the inner and downflows in the outer penumbra, actually at the inner and outer ends of penumbral filaments (Tiwari et al 2013). The downflows completely dominate over the upflows on the border between the penumbra and the granulation surrounding it, resulting in a clearly defined ring of downflows surrounding the entire sunspot.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…1, is the granular flow pattern that is clearly visible around both the sunspots. This contrasts with the penumbra, that shows many compact regions containing predominantly upflows in the inner and downflows in the outer penumbra, actually at the inner and outer ends of penumbral filaments (Tiwari et al 2013). The downflows completely dominate over the upflows on the border between the penumbra and the granulation surrounding it, resulting in a clearly defined ring of downflows surrounding the entire sunspot.…”
Section: Resultsmentioning
confidence: 88%
“…Such downflows are found at the ends of all penumbral filaments, although in the case of simple filaments, with a single head and a single tail, they only reach speeds of 6 km s −1 on average, so that many of them remain subsonic (Tiwari et al 2013). The supersonic downflows of this type are found at the ends of more complex filaments, particularly those with multiple heads that merge to form a single tail (or alternatively multiple filaments merge).…”
Section: Supersonic Downflowsmentioning
confidence: 99%
“…The flows also move the magnetic features around, causing each to carry out a random walk, although the exact nature of the motion can differ, depending on the location of the magnetic feature (Abramenko et al 2011;Jafarzadeh et al 2014a). Tiwari et al (2013) and van Noort et al (2013) The random walk of the magnetic patches, imposed by the convective motions, necessarily leads to the encounter of opposite polarity fields. These, in the case of smaller flux tubes, often do not correspond to the other footpoint of the original -loop, so that in larger ARs, a fair amount of cancelation takes place .…”
Section: Temporal Evolution Of the Magnetic Fieldmentioning
confidence: 99%
“…At the same time, Solanki & Montavon (1993) established that these two distinct components also interlace vertically, thereby explaining the asymmetries in the observed circular polarization profiles (Stokes V ). It was later found that the vertical and horizontal interlacing of these two components implies that the magnetic field in the spines wraps around the intraspines , with the latter remaining unchanged at all radial distances from the sunspot's center (Borrero et al 2005(Borrero et al , 2006Tiwari et al 2013) and the former being nothing but the extension of the umbral field into the penumbra (Tiwari et al 2015). It has also been confirmed that the Evershed flow can reach supersonic and super-Alvénic values, not only on the outer penumbra (Borrero et al 2005;van Noort et al 2013), but also close to the umbra (del Toro Iniesta et al 2001;Bellot Rubio et al 2004) and has a strong upflowing component at the inner penumbra that turns into a downflowing component at larger radial distances (Franz & Schlichenmaier 2009Tiwari et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It was later found that the vertical and horizontal interlacing of these two components implies that the magnetic field in the spines wraps around the intraspines , with the latter remaining unchanged at all radial distances from the sunspot's center (Borrero et al 2005(Borrero et al , 2006Tiwari et al 2013) and the former being nothing but the extension of the umbral field into the penumbra (Tiwari et al 2015). It has also been confirmed that the Evershed flow can reach supersonic and super-Alvénic values, not only on the outer penumbra (Borrero et al 2005;van Noort et al 2013), but also close to the umbra (del Toro Iniesta et al 2001;Bellot Rubio et al 2004) and has a strong upflowing component at the inner penumbra that turns into a downflowing component at larger radial distances (Franz & Schlichenmaier 2009Tiwari et al 2013). Finally, there is strong evidence for an additional component of the velocity field in intraspines that appears as convective upflows along the center of the intraspines that turns into downflows at the filaments' edges (Zakharov et al 2008;Joshi et al 2011;Scharmer et al 2011;Tiwari et al 2013).…”
Section: Introductionmentioning
confidence: 99%